Aging of Environmentally Friendly Alkyd Coating Containing Tinuvin 292 under Effect of UV Radiation - Nguyen Trung, Thanh (Hue University Journal of Science: Natural Science, 2023)
This study presents durability of environmentally friendly alkyd coating containing Tinuvin 292 (a liquid hindered amine light stabilizer) under UV-thermo-humidity condition. Coatings were accelerated under UV-thermo-humidity complex for 100 cycles. FT-IR, TGA and SEM were used to value the changes of before and after accelerated weathering tested coatings. Results showed that gloss loss, adhesion, flexural strength, impact resistance, relative hardness of tested coating were much improved with 1.5 weight percent (wt.%) of Tinuvin 292. FT-IR spectrums of initial and aged coatings without Tinuvin 292 illustrated the significant changes on intensity of CH2 and C=O (ester) groups. Meanwhile, coating with Tinuvin 292 exhibited that intensity of CH2 and ester groups had been changed slightly. SEM images indicated that surface morphology of samples changed differently depending on the presence Tinuvin 292. After aging process, surface of aged coating without Tinuvin 292 became worse than that of coating with Tinuvin 292. TGA also showed that 1.5 wt.% of Tinuvin 292 had improved thermo oxidation stability of environmentally friendly coating.